Enhanced Depth SD-OCT Images Reveal Characteristic Choroidal Changes in Patients With Vogt-Koyanagi-Harada Disease - Li, Mei (Ophthalmic surgery, lasers & imaging retina, 2016)
Copyright 2016, SLACK Incorporated.